Validating a Low-Fidelity Model for Microsurgical Anastomosis Training. Issue 3 (July 2021) - Mohammad, Saeed; Hanstein, Regina; Lo, Yungtai; Levy, I. Martin
Abstract : Background: With cost, size, and availability in mind, we developed a low-fidelity microsurgery anastomosis model for mastery of the tool skills needed to execute microsurgical procedures. The model combined the use of a cannulated Konnyaku Shirataki (KS) noodle with a low-cost, industrial inspection, trinocular stereo (IITS) microscope. The purpose of this study was to establish face and construct validity of this novel "combined" microsurgery training tool. Methods: Fifteen participants, divided into 3 groups based on microsurgery experience, attempted microsurgical anastomoses of a cannulated KS noodle using the IITS microscope. Participants were asked to (1) manipulate the noodle ends adjacent to each other, (2) place a single 7-0 nylon suture through the opposed ends, and (3) complete the anastomosis. To determine construct validity, the performance of the microsurgical repair (maximum score 53 points) and time-to-anastomosis was assessed. To determine face validity, microsurgeons were given a 25-item, 5-point scale survey rating their experience with the model. Results: Participants included 5 microsurgeons, 5 experienced trainees, and 5 novices. The microsurgeons judged the IITS microscope to be a close analog to an operating microscope (4.6/5 points), the combined model to have high educational value (4.7/5 points), and somewhat technical similarity with microsurgery in the operating room (OR) (3.7/5 points). The median technical score was 50 among microsurgeons, 40 among experienced trainees, and 27 among novices. Increased training level was associated with greater technical score among all 3 groups (p=0.002). The median time-to-anastomosis was 5.88 minutes for microsurgeons, 8.37 minutes for experienced trainees, and 17.10 minutes for novices. Increased training level was associated with shorter time-to-anastomosis (p=0.003). Conclusion: The use of the KS noodle with a benchtop stereo microscope is a novel approach to microsurgical training. It is inexpensive, available, conducive to high-repetition training, and suited to many learning environments. Microsurgeons found that this combined model was representative of microsurgery in the OR, and we concluded face validity. Furthermore, an association was demonstrated between training level and performance on the model, suggesting construct validity.